Morphological, phytochemical and molecular characterization of five common Jatropha species in the Niger Delta Region of Nigeria - B.A. Odogwu; J. Ukomadu; I. Igwe (Journal of Applied Sciences and Environmental Management, 2021)
The economic and medicinal important genus Jatropha contains many distinctly different species. To elucidate the genetic relationship of five common occurring Jatropha species namely J. multifida, J. podagrica, J. tanjorernsis, J. curcas, and J. gossypifolia, thirty-nine morphological, six phytochemical features and one arbitrary marker was used to screen and explore their similarity. Morphological data was obtained from the measurement of vegetative and reproductive parts while the presence of five phytochemicals was determined using different phytochemical tests. The DNA of all five Jatropha species were amplified and sequenced using Ribolose 1, 5- biphosphate carboxylase molecular marker. The DNA sequences were then aligned using the Basic Local Alignment Search Tool for nucleotide 2.8.0 version of the National Center for Biotechnology Information database and phylogenetic trees were constructed using Paleontological Statistical software and Molecular Evolutionary Genetics Analysis version 7.0.26 software. From the results of the classical and phylogenetic cluster analysis, the five Jatropha species was separated into two major clusters. The highly distinctive J. gossypifolia was the only species that clustered separately from the other Jatropha species. Although, J. tanjorensis has been reported to be a hybrid from J. curcas and J. gossypifolia, the species did not segregate and cluster with these species, but segregated with J. multifida, and J. podagrica, indicating that this species is more closely related to J. multifida, and J. podagrica than J. curcas and J.gossypifolia. The result therefore provide information that would be useful in the plant improvement programs for the genus Jatropha.